2020
DOI: 10.1177/1120672120925788
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes of intravitreal dexamethasone in relation to biomarkers in diabetic macular edema

Abstract: Purpose: The purpose of this study was to determine the effects of dexamethasone implant (0.7 mg) on biomarkers such as hyper-reflective dots, external limiting membrane integrity and disorganization of retinal inner layers in treatment-naïve patients, patients who received less than three anti-vascular endothelial growth factor injections and non-responder cases with diabetic macular edema and its effects on edema and visual acuity. Methods: This is a prospective study of treatment-naïve patients, patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…The results of the meta-analysis did not show a significant effect of baseline HRS on the change in visual acuity. However, eyes with treatment naive DME 15,16,[30][31][32]35,37,40 as against those with refractory DME 14,38,39 showed a positive correlation between HRS with VA gain (5/8 studies versus 0/3 studies) and CMT reduction (7/8 studies versus 1/3 studies). Also, eyes where HRS was associated with NSD at baseline responded better and showed a positive correlation between HRS and VA improvement and CMT reduction with in first 2-3 months.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…The results of the meta-analysis did not show a significant effect of baseline HRS on the change in visual acuity. However, eyes with treatment naive DME 15,16,[30][31][32]35,37,40 as against those with refractory DME 14,38,39 showed a positive correlation between HRS with VA gain (5/8 studies versus 0/3 studies) and CMT reduction (7/8 studies versus 1/3 studies). Also, eyes where HRS was associated with NSD at baseline responded better and showed a positive correlation between HRS and VA improvement and CMT reduction with in first 2-3 months.…”
Section: Discussionmentioning
confidence: 92%
“…Nineteen studies were identified (thirteen were retrospective cohort studies, 12,[15][16][17]24,26,[30][31][32][33][34][35][36] three were prospective cohort studies, 37,38,41 two were case series 14,39 and one was a case-control study 40 ). The quality score of the studies is shown in Table 1.…”
Section: Quality Of the Studiesmentioning
confidence: 99%
See 3 more Smart Citations